Intramedullary Nail Versus Plate Fixation for Humeral Shaft Fractures: A Systematic Review of Overlapping Meta-analyses - Zhao, Jia-Guo (Medicine (Baltimore), 2015)
Multiple meta-analyses have been published to compare intramedullary nail and plate for treating humeral shaft fractures; however, results are discordant. The purposes of current study were to perform a systematic review of overlapping meta-analyses comparing intramedullary nail and plate fixation for the treatment of humeral shaft fractures, to appraise the methodological quality and the quality of reporting of meta-analyses, and to propose a guide through the currently discordant available evidence. This systematic review was performed according to the guidelines of Preferred Reporting Items for Systematic Reviews and Meta-analysis. The literature was systematically reviewed to identify meta-analyses comparing intramedullary nail and plate fixation for the treatment of humeral shaft fractures. Only meta-analyses exclusively including randomized clinical trials (RCTs) met eligibility criteria in this systematic review. Methodological quality for each included study was assessed using the Oxford Levels of Evidence and the Assessment of Multiple Systematic Reviews Instrument. We extracted all variables from the included studies and listed the results reported by them. Heterogeneity information of each variable was extracted for the included studies. An I(2) of <60% is accepted in this systematic review. The Jadad algorithm was then applied to determine which meta-analyses provided the best evidence. Seven studies met the inclusion criteria in this study. All studies included RCTs or quasi-RCT and were Level II of evidence. Assessment of Multiple Systematic Reviews scores varied from 6 to 10 with a median of 7.86. Heterogeneity of each outcome was acceptable in those meta-analyses pooled results. The Jadad algorithm suggested that the meta-analyses can be selected based on the search strategies and application of selection. As a result, 2 meta-analyses with more RCTs were selected in this systematic review. The best available evidence suggested that the differences between intramedullary nail and plate fixation were not significant in fracture union, radial nerve injury, and infection. But intramedullary nail significantly increased the risk of shoulder complications (shoulder impingement and restriction of shoulder movement) and reoperation. We concluded that plate fixation is superior to intramedullary nail for the treatment of humeral shaft fractures.